1999
DOI: 10.1002/(sici)1097-4660(199906)74:6<509::aid-jctb68>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of zirconium and nickel byCitrobacter sp

Abstract: Zirconium in aqueous¯ows was moderately biomineralized by immobilized Citrobacter N14 cells, in the form of gel-like deposits, probably comprising a mixture of zirconium hydrogen phosphate (Zr(HPO 4 ) 2 ) and hydrated zirconia (ZrO 2 ). The simultaneous presence of uranyl ion (UO P P ) did not facilitate zirconium deposition and the biomineralization of uranium itself as HUO 2 PO 4 was repressed by zirconium in the presence of excess inorganic phosphate, liberated enzymatically. Nickel (Ni 2+ ) was not signi®c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…to a mixture of Zr(HPO 4 ) 2 and hydrated zirconia (ZrO 2 ): biomineralization of uranium as HUO 2 PO 4 was repressed by zirconium in the presence of excess inorganic phosphate. Cell-bound HUO 2 PO 4 facilitated Ni 2 + removal by intercalative ion exchange into the polycrystalline lattice and also promoted Zr removal (Brasnakova and Macaskie, 1999).…”
Section: Phosphatase-mediated Metal Precipitationmentioning
confidence: 98%
“…to a mixture of Zr(HPO 4 ) 2 and hydrated zirconia (ZrO 2 ): biomineralization of uranium as HUO 2 PO 4 was repressed by zirconium in the presence of excess inorganic phosphate. Cell-bound HUO 2 PO 4 facilitated Ni 2 + removal by intercalative ion exchange into the polycrystalline lattice and also promoted Zr removal (Brasnakova and Macaskie, 1999).…”
Section: Phosphatase-mediated Metal Precipitationmentioning
confidence: 98%
“…Other factors influencing this crystallisation process are the solubility product of the metal phosphate, the nature and concentration of the complexing ligand(s) present and the pH of the solution. Previous studies showed that, despite the low solubility products quoted in the literature, in practice tetravalent metal phosphates tend not to desolubilise readily due to the extensive hydrolysis of the tetravalent ion in solution (Yong and Macaskie 1998;Basnakova and Macaskie 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Determination of Zr was as described by Basnakova and Macaskie (1999), using Xylenol Orange, with a slight modification. The calibration was made from stock solution: ZrOCl 2 Á8H 2 O made to 1 mM in a solution comprising 1 ml conc.…”
Section: Spectrophotometric Analyses Of Metals and Phosphatementioning
confidence: 99%
See 1 more Smart Citation
“…HUP exhibits high proton conductivities and can be employed as a solid electrolyte in micro-ionic devices, such as sensors [1][2][3][4], batteries [5] and electrochromic displays [6][7]. Studies of this compound has been centered on the structure [8][9][10][11], reactivity [12][13][14][15], vibrational spectroscopy [16], synthesis and characterization of intercalation compounds with different cationic species [17][18][19], diffusion and protonic conductivity mechanism [20][21][22][23][24][25][26][27][28], and chemisorption properties of HUP bound to biomass of bacteria [29][30][31][32][33]. Photoluminescence properties [34][35][36][37][38][39], have also been investigated in the literature, but they are not analyzed in terms of restricted geometry [40][41][42][43][44][45]...…”
Section: Introductionmentioning
confidence: 99%